STRATEGI DAYLIGHTING PADA BANGUNAN MULTI-LANTAI DI ATAS DAN DI BAWAH PERMUKAAN TANAH - Danny Santoso Mintorogo (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 1999)
One of the common factor for Energy Saving on buildings has dealed a lot with the lightings on building, especially for multi level floors above and below grade. In order for saving energy on lightings, many daylighting strategies on multi floors building are being used and under-developed by many architects. This paper discusses the strategies of the daylighting techniques on multi floors building both above and below grade Abstract in Bahasa Indonesia : Strategi hemat energi sangat erat hubungan dengan faktor penerangan dalam bangunan, lebih-lebih pada bangunan berlantai banyak diatas atau dibawah permukaan tanah. Untuk menghemat pemakaian energi listrik dari penerangan ini, maka strategi-strategi penerangan alami